Validation of the adherence questionnaire for Brazilian chronic kidney disease patients under hemodialysis - Silvia Maria de Sá Basilio Lins (Revista Brasileira de Enfermagem, 2017)
Objective: To validate the evaluation questionnaire on adherence of chronic kidney disease (CKD) patients under hemodialysis. Method: We verifi ed the following psychometric properties of the instrument: reliability (stability and internal consistency) and validity (face, content, and construct). Results: The intraclass correlation coeffi cient reached a value of 0.98 for the adherence questions and 0.91 for the perception questions. Regarding the kappa of the 14 questions examined, 12 had a value > 0.8, whereas the Cronbach’s alpha had a value of 0.57. Experts ensured the face and content validity of the instrument, giving it an overall content validity index of 0.96. Construct validity, analyzed by Mann–Whitney test, was achieved as all domains showed a signifi cant association with p<0.01. Conclusion: We verifi ed, by the presented results, that the instrument has been validated for use in Brazil.